PROBLEM-BASED INTERACTIVE MEDIA ON CIRCLE’S TANGENT BY USING ADOBE FLASH CS6 - Kintoko Kintoko (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
This research is a developmental research, the purpose of this research is to produce a problem based mathematic learning media with Tangent Line to Circle for VIII grade Junior High School student by utilizing Adobe Flash SC6 on a Compact Disc (CD). This research was conducted to determine the quality of mathematics learning media in accordance with a good learning media which based on three aspects; Validity, Practicality an Effectiveness. The procedure of this research was using ADDIE model; Analysis, Design, Development, Implementation and Evaluation. The result of this research shown that Problem Based Interactive Mathematics Learning Media on Tangent Line to Circle for VIII Grade Junior High School fulfilled the criteria of good media quality. On validity aspect, the media got “Valid” category with average score 3,307 by material expert and got “Very Valid” category with average score 3,877 by media expert. On practicality aspect, validator determined that the media was applicable with minimal revision, teacher response to the media shown “Very Good” category with average score 3,404 and media learning implementation observation sheet analysis shown “Good” category with average score 3,333. On effectiveness aspect, students’ test result shows 85,19% student “Passed”, students’ mathematic solving ability shows “Good” category with average score 80,09 and also students’ positive response with 81,25% response